Using High-Fidelity Avatars to Advance Camera-based Cardiac Pulse Measurement - McDuff, Daniel; Hernandez, Javier; Liu, Xin; Wood, Erroll; Baltrusaitis, Tadas (IEEE Transactions on Biomedical Engineering, 2022)
Non-contact physiological measurement has the potential to provide low-cost, non-invasive health monitoring. However, machine vision approaches are often limited by the availability and diversity of annotated video datasets resulting in poor generalization to complex real-life conditions. To address these challenges, this work proposes the use of synthetic avatars that display facial blood flow changes and allow for systematic generation of samples under a wide variety of conditions. Our results show that training on both simulated and real video data can lead to performance gains under challenging conditions. We show strong performance on three large benchmark datasets and improved robustness to skin type and motion. These results highlight the promise of synthetic data for training camera-based pulse measurement; however, further research and validation is needed to establish whether synthetic data alone could be sufficient for training models.